2014
DOI: 10.5014/ajot.2014.008987
|View full text |Cite
|
Sign up to set email alerts
|

Self-Generated Strategic Behavior in an Ecological Shopping Task

Abstract: OBJECTIVES. The use of cognitive strategies optimizes performance in complex everyday tasks such as shopping. This exploratory study examined the cognitive strategies people with traumatic brain injury (TBI) effectively use in an unstructured, real-world situation. METHOD. A behavioral analysis of the self-generated strategic behaviors of 5 people with severe TBI using videotaped sessions of an ecological shopping task (Instrumental Activities of Daily Living Profile) was performed. RESULTS. All participants u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…Performance-based assessments allow a fuller observation of behavioural strategies, including issues like help seeking and self-correction. These are fuller and potentially more ecologically valid ways of assessing real-world cognitive performance, a point that is widely noted in the occupational therapy literature (e.g., Baum et al, 2008; Bottari, Shun, Le Dorze, Gosselin, & Dawson, 2014; Rogers et al, 1999). Typical testing in neuropsychological practice and research is individual (unprompted).…”
Section: Discussionmentioning
confidence: 99%
“…Performance-based assessments allow a fuller observation of behavioural strategies, including issues like help seeking and self-correction. These are fuller and potentially more ecologically valid ways of assessing real-world cognitive performance, a point that is widely noted in the occupational therapy literature (e.g., Baum et al, 2008; Bottari, Shun, Le Dorze, Gosselin, & Dawson, 2014; Rogers et al, 1999). Typical testing in neuropsychological practice and research is individual (unprompted).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the resources and services available at these stores, the authors (KA, JC, DD, EN, SR) discussed each item and rule on the preliminary Big-Store MET in relation to whether it was feasible across many sites (see Supplementary Appendix A for task and rule list). In addition, they reviewed the strategies and categorized these according to their previous work in which internal strategies were classified as those that were self-generated and relied on conscious mental manipulations and external strategies as those that relied on cues from the external environment (Bottari et al, 2014). Through this process, a revised version of the original Big-Store MET was developed.…”
Section: Methodsmentioning
confidence: 99%
“…However, the ecological validity of the VR-EAL would benefit from future work directly comparing the VR-EAL with true real-world functioning. For example, studies have shown that performance on real-world tasks (e.g., household chores) is significantly associated with self-ratings of instrumental activities of daily living (IADL) and independence questionnaires (Weakley, Weakley, & Schmitter-Edgecombe, 2019), which produce reliable and generalizable outcomes (Bottari, Dassa, Rainville, & Dutil, 2010;Bottari, Shun, Le Dorze, Gosselin, & Dawson, 2014). Thus, the predictive ability and/or veridicality of the VR-EAL could be further examined by investigating its relationship with real-world tasks and/or established IADL questionnaires in healthy older adults and/or clinical populations.…”
Section: Verisimilitude and Pleasantnessmentioning
confidence: 99%